2022
DOI: 10.1021/acsanm.2c01304
|View full text |Cite
|
Sign up to set email alerts
|

Lamellar MXene Nanofiltration Membranes for Electrostatic Modulation of Molecular Permeation: Implications for Fine Separation

Abstract: Nanofiltration membrane-based molecular separation has become an indispensable technology for fine sieving processes. However, the difficulty in regulating the separation performance restricts the applicability of these nanofiltration membranes in different separation systems. Herein, we will show that the separation performance of Ti 3 C 2 T x −MXene lamellar nanofiltration membranes on certain dye molecules can be modulated by employing external electrostatic fields. Specifically, for cationic dyes, the nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…It was also suggested that on top of the size-sieving ability of MXene membranes, their voltage-gated sieving ability could be used for dye separation benefiting from the electrostatic interactions between dyes and MXene, which are regulated by changing the applied external voltage. 235,236 Therefore, it reveals that the separation performance of MXene membranes can be enhanced via mean contribution of different driving forces.…”
Section: Membrane-based Separationmentioning
confidence: 99%
“…It was also suggested that on top of the size-sieving ability of MXene membranes, their voltage-gated sieving ability could be used for dye separation benefiting from the electrostatic interactions between dyes and MXene, which are regulated by changing the applied external voltage. 235,236 Therefore, it reveals that the separation performance of MXene membranes can be enhanced via mean contribution of different driving forces.…”
Section: Membrane-based Separationmentioning
confidence: 99%
“…The high rejection rates of dyes were also demonstrated as 93.1% for Congo red and 94.8% for aniline blue under the application of −3 V, suggesting the potential of these membranes for regulated water transport as well as water treatment. The electrostatic interactions between dye molecules and Ti 3 C 2 T x membranes were also shown to modulate the separation performance for nanofiltration membranes . The application of negative voltage to the membranes provided better sieving of cationic dyes but reduced the water permeation, whereas the positive voltage reduced the retention and improved the water flux.…”
Section: Applications Of Mxene-based Materials In Water Treatmentmentioning
confidence: 99%
“…The electrostatic interactions between dye molecules and Ti 3 C 2 T x membranes were also shown to modulate the separation performance for nanofiltration membranes. 43 The application of negative voltage to the membranes provided better sieving of cationic dyes but reduced the water permeation, whereas the positive voltage reduced the retention and improved the water flux. However, an opposite behavior was observed in the case of anionic dyes, irrespective of the electric field being positive or negative.…”
Section: Applications Of Mxene-based Materials In Water Treatmentmentioning
confidence: 99%
“…NF for GBnM membranes is typically governed by the following separation mechanisms: 52,53 (1) physical adsorption or chemical interaction (i.e., cation-π interaction) between solute molecules and the surfaces of mass transport channels, (2) molecular sieving controlled by size exclusion, and (3) the Gibbs-Donnan effect (i.e., electrostatic repulsion) between charged solutes and charged groups anchored to the membrane surface. These mechanisms are interconnected, and the last two modes are more important in NF processes.…”
Section: Gbnm Membranes For Nfmentioning
confidence: 99%
“…NF for GBnM membranes is typically governed by the following separation mechanisms: 52,53 (1) physical adsorption or chemical interaction ( i.e. , cation–π interaction) between solute molecules and the surfaces of mass transport channels, (2) molecular sieving controlled by size exclusion, and (3) the Gibbs–Donnan effect ( i.e.…”
Section: Gbnm Membranes For Nfmentioning
confidence: 99%